The Teddy Bear's dancing lesson. (Montreal, Canada : Tormont, 1992)
Tatty Ted show the Dance Teacher what he can do. 'You have two left feet I cannot possibly teach you the teacher said.
Keywords: Dancing -- Fiction; Bears -- Fiction; Children stories